2020
DOI: 10.1142/s0218271820500248
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology of a generalised version of holographic dark energy in presence of bulk viscosity and its inflationary dynamics through slow roll parameters

Abstract: The present study reports a reconstruction scheme of a Dark Energy (DE) model with higher order derivative of Hubble parameter, which is a particular case of Nojiri-Odintsov holographic DE [50] that unifies phantom inflation with the acceleration of te universe on late-time. The reconstruction has been carried out in presence of bulk-viscosity, where the bulk-viscous pressure has been taken as a function of Hubble parameter. Ranges of cosmic time t have been derived for quintessence, cosmological constant and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…We propose to carry out a similar viscous cosmology under the purview of modified theories of gravity in future with the background evolution as Barrow HDE. While concluding we would like to draw the attention of the readers to the previously published two works [22,23] by the authors of the present paper, where the inflationary cosmology was demonstrated through a scalar field model and a generalised version of HDE. In a similar manner we propose to investigate the slow roll parameters under the consideration of Barrow HDE with NO cut-off as the fluid responsible for the inflationary expansion.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We propose to carry out a similar viscous cosmology under the purview of modified theories of gravity in future with the background evolution as Barrow HDE. While concluding we would like to draw the attention of the readers to the previously published two works [22,23] by the authors of the present paper, where the inflationary cosmology was demonstrated through a scalar field model and a generalised version of HDE. In a similar manner we propose to investigate the slow roll parameters under the consideration of Barrow HDE with NO cut-off as the fluid responsible for the inflationary expansion.…”
Section: Discussionmentioning
confidence: 95%
“…The simplest candidate of DE is cosmological constant (Λ), characterised by EoS parameter w = −1 [13]. Various DE models have been reviewed in the literature [11,12,[14][15][16][17][18][19][20][21][22][23][24][25][26]. From References [27,28], currently the DE percentage is 68.3%.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that there are also other proposals of the cutoff scale such as using higher-order derivative of the Hubble parameter as the cutoff scale and etc. [121][122][123][124].…”
Section: Introductionmentioning
confidence: 99%
“…The DE and DM models developed by Odintsov 2005, 2006a) were treated as imperfect fluids. A plethora of literatures has suggested to us that the bulk viscous pressure plays a major role in the late time acceleration of the Universe (Brevik et al 2004(Brevik et al , 2010(Brevik et al , 2015Chakraborty & Chattopadhyay 2020a,c,b, 2021. The late time acceleration is not the only accelerated phase of the Universe.…”
Section: Introductionmentioning
confidence: 99%